Perspective Planning for Self-Assured Growth: An Approach to Foreign Capital from a Recipient's Point of View (The Pakistan Development Review, 1968)
The purpose of the present paper is to discuss the problem of dependence on foreign capital for economic growth of Pakistan, a typically under¬developed country which is relying rather heavily on foreign assistance without a sufficiently spelled-out analysis of the economic and political consequences of such a policy for the country's future. The discussion starts with an analysis of the implications of Pakistan's current Perspective Plan (1965-85) for plan-terminal external indebtedness of the country (Section II). Need for careful rationalization of a terminal bequest of liability of this magnitude to future society is stressed. This is followed by a discussion (Section III) of the alternatives the country would have to service the external indebtedness with which it would be saddled at termination of its Perspective Plan. It is pointed out that the alternatives have political implications for the country's future, and one may question the ethics of thus restricting choice of policies for future generations.